Self-Handicapping and Irrational Beliefs About Approval In A Sample of Teacher Candidates - (:unkn) unknown (My University, 2017)
Bu araştırmanın amacı kendini sabotaj ile onay, kişilerarası ilişkiler ve benlik ile ilişkili akıldışı inançlar ve genel akıldışı inanç düzeyleri arasındaki ilişkileri"ABC"çerçevesi kapsamında incelemektir. Araştırma grubu 263 öğretmen adayından oluşmaktadır. Yapıları ölçmek için Kendini Sabotaj Ölçeği ve Akıldışı İnançlar Ölçeği-Kısa Formu kullanılmıştır. Spearman Rho Korelasyon ve Mann Whitney U analizleri kullanılmıştır. Onay ile ilişkili 1. A previous version of the study was presented at the III. International Conference on Interdisciplinary Research on Education, October, 29-3, 2014 Milano.akıldışı inançlar ve genel akıldışı inanç düzeyinin kendini sabotaj ile anlamı düzeyde ilişkili bulunmuştur (sırasıyla r= .33 ve r= .18, p< .05). Sonuçlar onay ile ilişkili akıldışı inançlar ile kendini sabotaj arasında pozitif yönde bir ilişki olduğunu göstermektedir. Onay ile ilişkili akıldışı inançlar açısından cinsiyete göre anlamlı bir farklılık bulunmuştur. Sonuçlar ilgili alan yazın kapsamında tartışılmıştır.

The main objective of the current study is to examine the relationships between selfhandicapping, and irrational beliefs about approval, irrational beliefs about interpersonal relationships, irrational beliefs about self and the overall level of irrational beliefs by reference to the "ABC" framework. Participants of the study were 263 teacher candidates. SelfHandicapping Scale and Irrational Beliefs Scale-Short Form was utilized in order to measure the constructs. Spearman's Rho correlations and Mann-Whitney U analyses were conducted. Irrational beliefs about approval and general irrational beliefs levels significantly related with levels of self-handicapping (r= .33 and r= .18 respectively, p< .05). The results verified that self-handicapping scores related positively to the scores of irrational beliefs about approval. A gender difference with respect to levels of irrational beliefs about approval was also verified. The results were discussed within the scope of the related literature
Öğretmen Adaylarında Kendini Sabotaj ve Onay İle İlişkili Akıldışı İnançlar
Keywords: Eğitim, Eğitim Araştırmaları